2014
DOI: 10.12688/f1000research.2-256.v2
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biologic and pharmacologic role of docosapentaenoic acid n-3

Abstract: Fish oil contains a complex mixture of omega-3 fatty acids, of which eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA), and docosahexaenoic acid (DHA) are the three predominant forms. There has been a plethora of previous research on the effects and associations of fish oil supplementation with various clinical manifestations. While the majority of this work was focused on EPA and DHA as the active compounds, emerging research has begun to elucidate the specific role that DPA plays in these physiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Further research on human whole blood has confirmed these data [122,123]. The absence of EPA, DPA, or DHA in the circulation may be an independent predictor and risk marker of CVD [124].…”
Section: Omega-3 Polyunsaturated Fatty Acidsmentioning
confidence: 70%
“…Further research on human whole blood has confirmed these data [122,123]. The absence of EPA, DPA, or DHA in the circulation may be an independent predictor and risk marker of CVD [124].…”
Section: Omega-3 Polyunsaturated Fatty Acidsmentioning
confidence: 70%
“…This suggests that plasma irisin is directly associated not only with increased D6D activity but also with increased activity of elongation and desaturation steps following desaturation of linoleic acid to α‐linolenic acid. The results of previous studies suggest that docosapentaenoic acid can have additional health benefits in conjunction with other n‐3 FA , although one study found that a higher proportion of docosapentaenoic acid in plasma PL was associated with a higher cardiovascular risk profile in adults .…”
Section: Discussionmentioning
confidence: 99%
“…While studies in infants have suggested the role of ARA in combination with DHA on physical growth and cognitive development [47,48,49,50], more recent data indicate that ARA and its derivatives may also play key roles in cardiovascular, inflammatory and immune functions, which have not yet been adequately investigated [34]. Similarly, the potential role of DPA in cardiovascular disease, immune function and psychiatric and cognitive health needs further investigation [51]. …”
Section: Discussionmentioning
confidence: 99%